2014
DOI: 10.1108/ejm-09-2012-0505
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric influence of cognitive and affective country image on rational and experiential purchases

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 58 publications
(104 reference statements)
3
74
0
3
Order By: Relevance
“…Lee and Lockshin (2012) state that PCI works like other intangible cues such as price, where higher prices may signal better quality. Although previous research has shown that a product's country of origin is related to individuals' product evaluation and choice, findings regarding the actual impact appear to be inconsistent (Li, Wang, Jiang, Barnes, & Zhang, 2014). Therefore, as Li et al (2014) argue, there is a need for further studies to explore the antecedents, nuances, and conditions in which country of origin can influence individuals' behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…Lee and Lockshin (2012) state that PCI works like other intangible cues such as price, where higher prices may signal better quality. Although previous research has shown that a product's country of origin is related to individuals' product evaluation and choice, findings regarding the actual impact appear to be inconsistent (Li, Wang, Jiang, Barnes, & Zhang, 2014). Therefore, as Li et al (2014) argue, there is a need for further studies to explore the antecedents, nuances, and conditions in which country of origin can influence individuals' behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…De Nisco et al (2015) state that in PCI literature, country image is often operationalized through the following three components (see also Laroche et al, 2005;Papadopoulos, 1993;Papadopoulos et al, 2013;Li et al, 2014;Koubaa, Methamem, & Fort, 2015 Despite the theoretical appeal of the above conceptualization, most studies using the PCI approach have not considered the multidimensionality of country image when operationalizing the construct (Laroche et al, 2005;Koubaa et al, 2015). For example, according to Li et al (2015), most studies consider country image as a cognitive construct (see also Elliot, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Pemikiran obyektif dari motif rasional antara lain fungsi, kebutuhan, kualitas pelayanan, garansi, tersedianya bantuan teknis, pengiriman yang tepat waktu, keuntungan finansial, dan tahan lama. Motif rasional berdasarkan pada keinginan atau hasrat untuk menghemat waktu dan uang, meningkatkan keuntungan finansial, mendapat kualitas jasa, jaminan tahan lama dan kepastian keamanan dengan menggunakan analisis logika dan pemahaman (Li, Lu, Jiang, Barnes, Zhang, 2014).…”
Section: Motif Rasional Dan Keputusan Pembelianunclassified
“…Perasaan nyaman 3 Keputusan Pembelian adalah proses penentuan pilihan konsumen dari berbagai alternative pilihan yang ada terhadap produk yang paling sesuai dengan kebutuhan yang diinginkan. Sumber: modifikasi dari Li et al, 2014;Yusa (2015); Hoque et al, (2012); Pentina et al, (2008).…”
Section: Tabel 1 Operasionalisasi Variabel Nounclassified